2003
DOI: 10.1177/03635465030310012801
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Anterior Cruciate Ligament Deficiency and Functional Bracing on Translation of the Tibia Relative to the Femur during Nonweightbearing and Weightbearing

Abstract: This study explains why subjects with anterior cruciate ligament tears gain partial control of pathologic anteroposterior laxity with the use of a brace but may continue to experience abnormal translations during activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 23 publications
1
45
1
Order By: Relevance
“…Subsequent knee injuries among skiers were found to be 6.4 times more likely in unbraced skiers. Interestingly, functionally braced skiers demonstrated greater degrees of anteroposterior laxity, which contrasts with findings by Beynnon et al, 6 who found that functional bracing led to lesser degrees of laxity.…”
Section: Evidence For Bracing Of High-risk Individualscontrasting
confidence: 84%
See 2 more Smart Citations
“…Subsequent knee injuries among skiers were found to be 6.4 times more likely in unbraced skiers. Interestingly, functionally braced skiers demonstrated greater degrees of anteroposterior laxity, which contrasts with findings by Beynnon et al, 6 who found that functional bracing led to lesser degrees of laxity.…”
Section: Evidence For Bracing Of High-risk Individualscontrasting
confidence: 84%
“…[6][7][8][9] Human and surrogate models have been used to confirm the effects of bracing. Using arthroscopy, Beynnon et al, 7 implanted transducers into the ACL of patients to measure strain.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 Bracing was, however, not effective in reducing abnormal anteroposterior laxity during the transition from nonYweight bearing to weight bearing, which was noted to be the period of greatest instability. This may explain why braced patients continue to have anteroposterior instability during physical activity.…”
Section: Functional Knee Bracingmentioning
confidence: 88%
“…Biomechanical studies reported that knee stability does not restore by wearing functional knee braces under high forces related to challenging activities (7). Beynnon et al (17) showed that knee bracing was effective to reduce abnormal anteroposterior laxity in patients with chronic ACLtear in static conditions. However, they reported that braces were not effective in reducing the abnormal translations in dynamic conditions.…”
Section: Discussionmentioning
confidence: 99%